2007
DOI: 10.1177/1049732306298380
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Multidisciplinary Divides: Exploring Professional Hierarchies and Boundaries in Focus Groups

Abstract: Focus groups are an important element of qualitative health research, valued for the forms of knowledge and understanding that emerge from interactions among participants. Common advice for focus groups within health research is to limit the level of variation among respondents to generate comprehensive discussion and shared knowledge. In this article, the authors critically examine this advice, proposing instead that it is useful to acknowledge and, at times, consciously build in heterogeneity across categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…Collaboration exists on a continuum; with no communication between professionals at one end, moving to referrals with limited communication and ultimately to service integration at the other [27,28]. Evidence from the literature emphasises a need for health professionals to understand and respect each others’ skills and opinions in order to promote professional engagement and collaboration [29]. Therefore, interdisciplinary care becomes key to improving health outcomes, possibly highlighting the need for families with young children to have more contact with an appropriate health professional, such as Child and Family Health Nurses and not necessarily the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration exists on a continuum; with no communication between professionals at one end, moving to referrals with limited communication and ultimately to service integration at the other [27,28]. Evidence from the literature emphasises a need for health professionals to understand and respect each others’ skills and opinions in order to promote professional engagement and collaboration [29]. Therefore, interdisciplinary care becomes key to improving health outcomes, possibly highlighting the need for families with young children to have more contact with an appropriate health professional, such as Child and Family Health Nurses and not necessarily the GP.…”
Section: Discussionmentioning
confidence: 99%
“…She suggested that conflict is most effectively managed by acknowledging and normalising it and identifying its source. Clavering and McLaughlin (2007) suggested finding opportunities for professional groups to discuss how they view themselves and others in the particular health context, in this way, professional boundaries become visible and tensions can be addressed.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the literature [14], we endeavoured to ensure a minimum of 4 and maximum of 12 participants per focus group; however, one of the carer groups only involved 3 people. We felt it was essential to run two separate carers groups to compare and contrast the responses from the two groups and to reduce the possibility of one-person dominance which sometimes occurs in focus groups [15].…”
Section: Data Collectionmentioning
confidence: 99%